Mechanical Engineering for Society and Industry: A Preface - Heri Hermansyah; Lukman Lukman; Harun Joko Prayitno; Lilik Andriyani; Yun Arifatul Fatimah (Universitas Muhammadiyah Magelang, 2021)
In a research cycle, researchers need to publish their work and readers expect reliable arguments and information. Seeing society and industry needs relate to mechanical engineering for now and in the future, Mechanical Engineering for Society and Industry (MESI) is an important journal to discuss problems and solutions in mechanical engineering practice. The articles in this journal are a representation of scientific editors and advisory boards' dedication, reviewers' contributions in improving articles quality, and authors contributions in providing standardized articles. Hopefully, this journal can be a source of new insights and inspiration for further research, as well as a new reference for society and industry to solve their problems.